Preschoolers Focus on Others’ Intentions When Forming Sociomoral Judgments - Van de Vondervoort, Julia W.; Hamlin, J. Kiley (Frontiers in Psychology, 2018)
Many studies suggest that preschoolers initially privilege outcome over intention in their moral judgments. The present findings reveal that, in contrast, even younger preschoolers can privilege intentions when evaluating characters who successfully or unsuccessfully help or hinder a third party in achieving its goal. Following a live-action puppet show originally created for infant populations, children made a forced-choice social judgment (which puppet was liked) and two forced-choice moral judgments (which puppet was nicer, which puppet should be punished), and were asked to explain their punishment allocations. In two experiments (N=195), 3- and 4-year-olds evaluated characters with distinct intentions to help or to hinder who were associated with either positive or negative outcomes. Both ages judged characters with more positive intentions as nicer, and allocated punishment to characters with more negative intentions; neither of these tendencies depended on the outcomes the characters were associated with. Three-year-olds’ responses were somewhat less consistent than were 4-year-olds’, in that 3-year-olds’ judgments were disrupted by ambiguous harmful intent. Notably, children’s social judgments were less consistent than their moral judgments. In a third and final experiment (N=100), children evaluated characters with the same intention but who were associated with different outcomes. Children showed inconsistent responding across age and outcome valence, but only 4-year-olds evaluating two characters with positive intentions reliably responded based on outcome. When providing informative responses in all three studies, children most frequently explained their punishment allocations by appealing to the puppet’s (attempted) hindering action or failure to help. These findings raise questions as to what underlies different patterns of response across studies in the literature, and suggests that observing live interactions may facilitate young children’s intention-based moral judgments.